Development of Balinese Cosmetology Marketplace Application on Android Based - Wirdiani, Ayu; Sudana, Oka (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 11 No 3 (2023): Vol. 11, No. 3, December 2023DO - 10.24843/JIM.2023.v11.i03.p08, 2023)
Appearance is the main thing for women. An attractive appearance makes a person more confident. This shows that the demand for personal beautification services is still high, and is a promising beauty business opportunity. Apart from daily grooming, salon and cosmetology businesses are also in high demand at certain events such as graduations, weddings and dance events. In the pandemic era, most people are reluctant to leave the house to get treatment, they want something practical that can be ordered online. Based on this, a solution was created in the form of an online application so that people can order make-up and body care at home. In this application there will be three users, namely salon admin, customer and therapist staff. The test results using the black box method which were tested by 15 salon customers produced a percentage of 87.96%, which means the application is very suitable for development. The test results with usability testing show that the satisfaction indicator is the highest indicator.